2018
DOI: 10.26493/1854-6935.16.141-157
|View full text |Cite
|
Sign up to set email alerts
|

Time-Frequency Analysis of CAPM: Application to the CAC 40

Abstract: The market line estimation implicitly assumes that its parameters are constant over time supposing whatever the investment horizon, the investors have a similar behaviour. In this paper, we discuss this hypothesis using the technique of wavelets. First, we verify the expected result concerning the statistical weaknesses of market line and the high volatility of its parameters. Second, we use the wavelets to estimate the frequency betas. We show that the classic beta (estimated with ols) considers a short-run b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Previously, we test the stationarity of risk premia (See Mestre and Terraza 2018) and we find that all variables have no unit‐root. Results are in Appendix A.…”
Section: Market Line Ols Estimationsmentioning
confidence: 82%
“…Previously, we test the stationarity of risk premia (See Mestre and Terraza 2018) and we find that all variables have no unit‐root. Results are in Appendix A.…”
Section: Market Line Ols Estimationsmentioning
confidence: 82%
“…Their results imply that the risk-profile (of a portfolio or a stock) is frequency dependent because the beta is frequency-varying. Mestre and Terraza ( 2018 ), McNevin and Nix ( 2018 ), Shah et al ( 2018 ), and Sakemoto ( 2020 ) all confirmed that systematic risk is conditional on an investment horizon (frequencies). These studies also discovered that frequency dynamics differ across industries.…”
Section: Introductionmentioning
confidence: 83%